Towards Research University through Ambidexterity Practice: A Lecturer Perspective - Retno Kusumastuti; Nurul Safitri; Prima Nurita Rusmaningsih (Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
The concept of ambidexterity in organization theory refers to an organization's ability to innovate in explorative manners (Duncan, 1980). Ambidexterity can be identified into structural ambidexterity and contextual ambidexterity (Tushman, O'Reilly, 1990). In small medium enterprises, for example, innovation activities take contextual form since most owners act both as entrepreneurs and business leaders (Kusumastuti, et.al., 2015), while in established corporations innovation activities generally occur in structural form. Thus research takes academic institution as its locus, within which innovation activities are mandatory for all civitas academica (academic community). The study uses mixed method for collecting data through questionnaires and in-depth interviews. It shows that university has the capacity to provide context in institutional support and remuneration system as a means stimulate lecturers and researchers to be more innovative. The scheme also provided structure at the university and faculty level as tools to coordinate and integrate research projects. The organizational learning at the individual level reflects the pattern of contextual ambidexterity process.